Effects of pressure gradient on convective heat transfer in a boundary layer flow of a Maxwell fluid past a stretching sheet - Salah, Faisal; Kashif, A.N.; Sankar, D.S.; Izyan, Nurul Mat Daud; Viswanathan, K.K. (Zielona Góra: Uniwersytet Zielonogórski)
The pressure gradient term plays a vital role in convective heat transfer in the boundary layer flow of a Maxwell fluid over a stretching sheet. The importance of the effects of the term can be monitored by developing Maxwell`s equation of momentum and energy with the pressure gradient term. To achieve this goal, an approximation technique, i.e. Homotopy Perturbation Method (HPM) is employed with an application of algorithms of Adams Method (AM) and Gear Method (GM).
Keywords: Homotopy Perturbation Method (HPM); pressure gradient parameter; convective heat transfer; Maxwell fluid; stretching sheet